A comparative study of P1 and fuzzy logic automatic voltage regulator of a micro-alternator system - Jamaan, Saiful; Majid, Md. Shah; Mustaffa, Mohd. Wazir; Abdul Rahman, Hasimah (2004)
A micro-computer based PI and fuzzy logic automatic voltage regulator is applied to a micro-alternator system. This paper describes the design and implementation of PI and Fuzzy Logic automatic voltage regulator of a micro-alternator. A comparative study of P1 and Fuzzy Logic AVK is analyzed and results show that the Fuzzy Logic improves the system damping subject to disturbances. Borland Delphi is used to develop the software algorith for the controller.